2022
DOI: 10.3389/fphar.2022.845196
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Elephant Grass (Cenchrus Purpureus (Schumach.) Morrone) via Activation of PI3K/AkT Signaling Pathway, Oxidative Stress Inhibition, and Apoptosis in Wistar Rats

Abstract: Ethnopharmacological Relevance: The management of diabetes over the years has involved the use of herbal plants, which are now attracting interest. We assessed the antidiabetic properties of aqueous extract of C. purpureus shoots (AECPS) and the mechanism of action on pancreatic ß-cell dysfunction.Methods: This study was conducted using Thirty-six 36) male Wistar rats. The animals were divided into six equal groups (n = 6) and treatment was performed over 14 days. To induce diabetes in the rats, a single dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
6
16
0
Order By: Relevance
“…48 Reports have shown that kaempferol inhibits gluconeogenesis and enhances glucose metabolism. 49 The anti-diabetic activity of anthocyanidins is mainly by promoting insulin secretion and improving insulin resistance by reducing the levels of triacylglycerol, cholesterol, low-density lipoprotein, and apolipoprotein levels. 40 Thus, the therapeutic efficacy of L hastata could be anchored on these phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Reports have shown that kaempferol inhibits gluconeogenesis and enhances glucose metabolism. 49 The anti-diabetic activity of anthocyanidins is mainly by promoting insulin secretion and improving insulin resistance by reducing the levels of triacylglycerol, cholesterol, low-density lipoprotein, and apolipoprotein levels. 40 Thus, the therapeutic efficacy of L hastata could be anchored on these phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Accordingly, the regulation of postprandial blood glucose is one of the most important therapeutic targets for DM treatment. 49 Its reduction using the inhibitors of α-amylase and α-glucosidase in T2D patients decreases glycated hemoglobin levels and prevents diabetic complications. 58 The results obtained in this study showed that L hastata extracts demonstrated the ability to reduce PPHG by inhibiting the activities of α-amylase and α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…We isolated total RNA from the liver and pancreas following the procedure illustrated by Ojo et al . [ 24 , 44 ]. TRIzol reagent (Zymo Research, USA, Cat: R2050-1-50, Lot: ZRC186885) was used to homogenize the liver and pancreas at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…We used the protocol illustrated in Ojo et al . to perform PCR intensification for the evaluation of genes whose primers (Primer3 software) are listed below [ 24 , 44 ]. In a 25 μl volume mixture of 2 μl cDNA (10 ng), 2 μl primer (100 pmol), and 2 μl water, PCR enhancement was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…However, an experimental study showed that chloroquine could cross the placenta and accumulate in the fetal eyes, and remained for up to five months after clearance from the body [ 75 ]. Similarly, a very high dose of ≥ 250 mg/kg of chloroquine during pregnancy was found to increase the risk of developing anophthalmia and microphthalmia in rats [ 75 77 ]. According to the current literature, the effectiveness of chloroquine and hydroxychloroquine is of limited value in COVID-19 [ 78 , 79 ].…”
Section: Management Of Covid-19 During Pregnancymentioning
confidence: 99%